Inauguration of the proceedings - Conso, Giovanni (PSL Quarterly Review, 2012)
A little more than a year after the death of Franco Modigliani, the Accademia Nazionale dei Lincei felt compelled to devote, in agreement with the Bank of Italy and its Governor, his partner in this world-renowned an international conference. JEL Codes: E20, E40, E50